A simple one-pot 2-step N-1-alkylation of indoles with α-iminoketones toward the expeditious 3-step synthesis of N-1-quinoxaline-indoles - Martinez-Ariza, Guillermo (2013)
A straightforward procedure for the preparation of N-quinoxaline-indoles is presented. A base-catalyzed one-pot addition of indoles to a preformed α-iminoketone proceeds on the N-1 indole and the subsequent adduct undergoes an acid-mediated deprotection of an internal amino nucleophile, intramolecular cyclization and final oxidation generating N-1-quinoxaline-indoles in good yield.